INTEGRATING INSTITUTIONAL ARCHITECTURE AND DIGITAL MONITORING IN THE GOVERNANCE OF YOUTH WORK IN HIGHER EDUCATION: A SYSTEMS-BASED FRAMEWORK AND MATURITY MODEL FOR UZBEKISTAN - Ziyoda A. Aripova; Zafarova Sariya Rustamovna (TADQIQOTLAR, 2026)
Abstract: Uzbekistan’s higher education system has expanded from roughly nine per cent gross enrolment in 2017 to about forty-two per cent in 2025, and the Uzbekistan-2030 Strategy sets a target of at least fifty per cent. This rapid growth has pushed the management of youth work — the organised support of students’ social, civic, professional and psychological development — to the centre of institutional agendas, yet the governance of this domain remains uneven and weakly theorised. Purpose. The study develops and argues for an integrated framework that unifies three threads usually treated separately in the literature: the systems-theoretic understanding of youth work, the institutional architecture of universities, and the digital monitoring of student engagement. Methods. A qualitative, conceptual-analytical design combined a structured review of national and international sources, comparative analysis of foreign practice, content analysis of regulatory documents, and semi- structured expert interviews with managers, educators and psychologists at three higher education institutions in Tashkent, supported by direct observation of extracurricular activity. Results. Three reinforcing directions of development were identified — digital management technologies, socio-psychological approaches, and integrated monitoring — alongside persistent fragmentation, formalistic evaluation and a shortage of specialised personnel. Building on these findings, the paper proposes the Integrated Digital–Institutional Governance (IDIG) framework and an accompanying five-level Youth-Work Governance Maturity Model. Conclusions. Effectiveness depends less on adding activities than on connecting them: a shared governance core, a common data layer and adaptive feedback move institutions from fragmented, reactive practice toward data-informed, anticipatory governance. The framework offers a transferable diagnostic and design tool for systems undergoing comparable expansion.